2009
DOI: 10.1029/2009gl040663
|View full text |Cite
|
Sign up to set email alerts
|

THEMIS observation of multiple dipolarization fronts and associated wave characteristics in the near‐Earth magnetotail

Abstract: [1] Multiple dipolarization fronts were observed by THEMIS spacecraft in the near-Earth magnetotail during a substorm. The dipolarization fronts were located at the leading edge of earthward propagating plasma bubbles. Major energetic electron flux enhancements were observed at the dipolarization fronts, which were also associated with large wave fluctuations extending from below the lower hybrid frequency to above the electron cyclotron frequency. Intense electric field wave packets, primarily contributed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
259
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 189 publications
(280 citation statements)
references
References 35 publications
(31 reference statements)
18
259
0
3
Order By: Relevance
“…2. It is seen from the figure that the B Z pulses have the typical characteristics of DFs, such as the rapid increase of the B Z component preceded by the negative B Z variation, the decrease in density behind the front, and the decrease in plasma pressure, while magnetic pressure increases across the front (e.g., Shiokawa et al, 2005;Zhou et al, 2009;Runov et al, 2009). Grigorenko et al (2018) studied the magnetic gradients observed by closely located C3 and C4 in the vicinity of the strongest B Z pulse detected by C4 at ∼ 01:39:41 UT.…”
Section: Data Descriptionmentioning
confidence: 99%
See 3 more Smart Citations
“…2. It is seen from the figure that the B Z pulses have the typical characteristics of DFs, such as the rapid increase of the B Z component preceded by the negative B Z variation, the decrease in density behind the front, and the decrease in plasma pressure, while magnetic pressure increases across the front (e.g., Shiokawa et al, 2005;Zhou et al, 2009;Runov et al, 2009). Grigorenko et al (2018) studied the magnetic gradients observed by closely located C3 and C4 in the vicinity of the strongest B Z pulse detected by C4 at ∼ 01:39:41 UT.…”
Section: Data Descriptionmentioning
confidence: 99%
“…The strong B Z pulses had characteristics typical of DFs, such as the rapid increase of the magnetic field B Z component preceded by small negative B Z variation, the decrease in density behind the front and the decrease in plasma pressure while magnetic pressure increases across the front (e.g., Shiokawa et al, 2005;Zhou et al, 2009;Runov et al, 2009) (see Fig. 2).…”
Section: Summary Of the Dipolarization Event Featuresmentioning
confidence: 99%
See 2 more Smart Citations
“…DFs are identified by a sharp increase of B z GSM and are associated with electron and ion acceleration [Asano et al, 2010;Zhou et al, 2010;Fu et al, 2011] as well as various wave activities, e.g., electron holes, whistler, lower hybrid, and electron cyclotron waves [Le Contel et al, 2009;Sergeev et al, 2009;Zhou et al, 2009;Deng et al, 2010;Khotyaintsev et al, 2011;Hwang et al, 2011].…”
Section: Introductionmentioning
confidence: 99%